Prospects of Development of Emulsion Sausages from Mince of Indian Major Carps - Gore, Sandeep; Balange, Amjad; Markad, Adinath; Relekar, Shailendra; Belsare, Sachin; Ghatge, Swapnil; Telvekar, Prashant; Joshi, Sagar (International Journal of Bio-resource and Stress Management, 2023)
The investigation was carried out during the year 2019 at Central Institute of Fisheries Education, Mumbai, India for the development of fish sausages . The objective of the research was to study the characteristics of fish muscle of Indian major carps (Labeo catla, Labeo rohita, Cirrhinus mrigala) for development of fish products such as sausages. The prepared sausages were heat processed at 40°C for 30 m followed by at 90°C for 20 m. Presence of sarcoplasmic proteins in the mince impaired quality of sausages made from Indian major carps. The highest gel strength (146.05 g.cm) and water holding capacity (89.68%) was obtained in sausages made from mince of mrigal fish. Higher hardness was observed in mrigal sausages which were in concomitant with the highest gel obtained in the present study. Higher cohesiveness was recorded for catla sausages whereas, higher adhesiveness was noticed in rohu sausages. Significant variation (p>0.05) in textural parameter were not observed among sausages made from mince of Indian major carps. Ingredients such as corn starch, sunflower oil used during preparation of sausages significantly affected colour properties of resultant sausages. Sausages made from mrigal fish were more white and lighter in colour than others. Among Indian major carps, sausages made from mince of mrigal fish showed better quality in terms of gel strength, hardness and were more yellowish in colour. Overall, freshness of fish greatly affected the quality characteristics of sausages made from mince of Indian major carps.